First detection and full genome sequence of porcine circovirus type 3 in Russia - Yuzhakov, Anton G.; Raev, Sergei A.; Alekseev, Konstantin P.; Grebennikova, Tatiana V.; Verkhovsky, Oleg A.; Zaberezhny, Alexei D.; Aliper, Taras I. (Virus genes, 2018)
Porcine circovirus type 3 (PCV3) was firstly detected in 2016 in USA. Later PCV3 was discovered in Asia, Europe, and South America. The present investigation demonstrates for the first time the circulation of PCV3 among pigs in Russia. The viruses were detected at two geographically distant unrelated commercial farms with records of reproductive failure (abortions, stillbirth), porcine dermatitis, and nephropathy syndrome (PDNS). The two farms were located in the region of Smolensk (western part of Russia) and the region of Tyumen (West Siberia, Russia). We investigated samples collected from pigs of different ages. We performed PCR for the PCV3 DNA detection. The DNA of PCV3 was detected in serum, kidney, heart, spleen, pleural effusion, and peritoneal cavity fluid samples. Two viral genomes were sequenced and the corresponding strains were named PCV3-RU/SM17 (the strain from Smolensk region) and PCV3-RU/TY17 (the strain from Tyumen region). The full genome sequences of both strains were 2000 nucleotides in length and contained at least two ORFs, encoding the Cap and Rep proteins. Full sequence alignment revealed a 99.3% identity between the PCV3-RU/SM17 and PCV3-RU/TY17 strains. Molecular analysis showed that the two strains from Russia are highly homologous to viruses identified in other countries, with a 98.5–99.6% homology for PCV3-RU/TY17 and 97.9–99.0 for PCV3-RU/SM17. The PCV3-RU/SM17 and PCV3-RU/TY17 strains were found to form a monophyletic group in a phylogenetic tree based on PCV3 complete genome sequences.